Review on: relevance of breast cancer recurrence with body mass index or obesity - Jangir, Narendra; Kchhawa, Devi Singh (International Surgery Journal, 2022)
Breast cancer is considered to be the second most life taking malignancy after lung cancer in the world. Some studies also show that changed lifestyle including alcohol and junk food is also increasing incidence or prevalence. Obesity is one of the side effects of the changed lifestyle so it can be a key to evaluate the relationship between obesity and breast cancer. Recurrence happens in about 40% of the breast cancer cases and is lethal too. Besides the treatments developed, breast cancer mortality still is increasing. Relationship of obesity and breast cancer is in such a way that obesity is not responsible for the causing of cancer but obesity can increase the risk of recurrence or improper treatment due to higher level of hormones which may directly or indirectly affect the pathways.